MOF‐Derived Porous ZnO/ZnFe2O4/C Octahedra with Hollow Interiors for High‐Rate Lithium‐Ion Batteries. (14th August 2014) - Zou, Feng; Hu, Xianluo; Li, Zhen; Qie, Long; Hu, Chenchen; Zeng, Rui; Jiang, Yan; Huang, Yunhui
<x xml:space="preserve">Abstract</x> Novel porous ZnO/ZnFe2O4/C octahedra with hollow interiors are fabricated by a facile self‐sacrificing template method involving the refluxing synthesis of hollow, metal‐organic framework octahedra in solution and subsequent thermal annealing in N2. When evaluated as an anode material for lithium‐ion batteries, these porous hollow ZnO/ZnFe2O4/C octahedra exhibit significantly enhanced electrochemical performances with high rate capability, high capacity, and excellent cycling stability. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>